If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + rt + 1 = 0 Reorder the terms: 1 + X + rt = 0 Solving 1 + X + rt = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + X + -1 + rt = 0 + -1 Reorder the terms: 1 + -1 + X + rt = 0 + -1 Combine like terms: 1 + -1 = 0 0 + X + rt = 0 + -1 X + rt = 0 + -1 Combine like terms: 0 + -1 = -1 X + rt = -1 Add '-1rt' to each side of the equation. X + rt + -1rt = -1 + -1rt Combine like terms: rt + -1rt = 0 X + 0 = -1 + -1rt X = -1 + -1rt Simplifying X = -1 + -1rt
| 8y+12=2(4y+6) | | (40-12x)-(48-15x)=1 | | 10y-xy=40x | | 3m^2=147 | | 0.5x^2-6x+22=0 | | x^5-3x^3-x^2-4x-1=0 | | 21(x-1)-14(x-1)=12x | | (3*y)*11=38y | | f(x)=x^5-8x^2+4x+48 | | ln(x)+ln(5x)=1 | | 10y=40x+xy | | x^2-16x+84=0 | | 9x-6=-3(x+2) | | 2-5/x=3/x^2 | | 2(x-1)=x+12 | | 5y*2y=10y | | x/3+x/4=49/12 | | 1x-15=2x-8 | | -6+5(-2)= | | 3(2x-4)+1=5(x+2) | | (4x+25)=(2x+5) | | 7(x+2)=13x-13 | | 6(x-4)=84-6x | | 4=0.088 | | 2(cos^2)4x-1=0 | | 24x^2-24x+48=0 | | y=1E+10e-0.066 | | -9(w-4)=-6w+6 | | 6x-5=73-7x | | 8.6d+6=3.3d+42.57 | | x(2x+6)=56 | | 2(4z+2)-6=54 |